The last man on earth [videorecording (DVD)] - Salkow, Sidney, 1909-2000; Price, Vincent, 1911-1993; Bettoia, Franca, 1936-; Danieli, Emma, 1936-1998; Matheson, Richard, 1926-2013 (Madacy Entertainment Group, 2003)
Thinking himself the only person alive after a plague that has also killed his wife and child, a scientist fights a nightly battle with what appear to be vampires, trying to break into his house.